2009
DOI: 10.1136/oem.2008.043380
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of mobile phone output power in a multinational study: implications for exposure assessment

Abstract: Average power levels are substantially higher than the minimum levels theoretically achievable in GSM networks. Exposure indices could be improved by accounting for average power levels of different telecommunications systems. There appears to be little value in gathering information on circumstances of phone use other than use in very sparsely populated regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 40 publications
4
45
0
1
Order By: Relevance
“…For each of the considered exposure circumstances, average specific absorption rates (SAR) for the brain and the whole body were derived from the literature (Gati et al 2009;Hadjem et al 2010;Huang et al 2014;Lauer et al 2013;Persson et al 2012;SEAWIND 2013;Vrijheid et al 2009). To obtain a cumulative daily brain and whole body dose for each study participant, the SAR values were multiplied by the average exposure duration per day for each exposure situation and summed up to one single brain and whole body dose measure.…”
Section: Rf-emf Dose Measuresmentioning
confidence: 99%
“…For each of the considered exposure circumstances, average specific absorption rates (SAR) for the brain and the whole body were derived from the literature (Gati et al 2009;Hadjem et al 2010;Huang et al 2014;Lauer et al 2013;Persson et al 2012;SEAWIND 2013;Vrijheid et al 2009). To obtain a cumulative daily brain and whole body dose for each study participant, the SAR values were multiplied by the average exposure duration per day for each exposure situation and summed up to one single brain and whole body dose measure.…”
Section: Rf-emf Dose Measuresmentioning
confidence: 99%
“…For each of these exposure situations, specific absorption rates (SAR) for the brain and the whole body were obtained from the literature (Gati et al 2009;Hadjem et al 2010;Huang et al 2014;Lauer et al 2013;Persson et al 2012;SEAWIND 2013;Vrijheid et al 2009). To obtain a brain and whole body dose for each study participant the obtained SAR values were multiplied by the average exposure duration per day for each exposure situation and summed up to one single brain and whole body dose.…”
Section: Rf-emf Dose Measuresmentioning
confidence: 99%
“…The denser the network, the more handovers or location area updates have to be expected. A recent European study with software modified mobile phones found that the average output power was approximately 50% of the maximal value, and that output power varied up to a factor 2 to 3 between countries and network operators (Vrijheid et al 2009). …”
Section: Introductionmentioning
confidence: 99%